Coping with religious tolerance and gender equality: comparing Islam and good governance perspectives - Ridho Al-Hamdi (Indonesian Journal of Islam and Muslim Societies, 2015)
Using  literature  review  and  in-depth  analysis,  the  study  is  going  to  examinethe  comparative  perspective  between  Islam  and  the West  in  addressing  twomain public  issues,  i.e.  religious  tolerance  and  gender  equality. More  specifi-cally, this study will provide the policy, agenda and strategy of Islam and goodgovernance  in  coping with  those  two  issues. Therefore,  the  finding  of  thestudy is that Islam and good governance precisely have no distinctive concept,policies, agendas and  strategy.  In contrast, both of  them obviously agree  thatreligious  tolerance  and  gender  equality  is  important  for  human  lifesustainability. The  result, Muslim  communities have  to  disseminate  the no-tion of  the  compatibility between  Islam  and  good  governance  to  the world.Menggunakan  review  literatur  dan  analisis mendalam,  penelitian  ini  akanmenguji  perspektif  komparatif  antara  Islam  dan Barat  dalam menjawab  duamasalah umum utama , yaitu toleransi beragama dan kesetaraan gender . Lebihkhusus,  penelitian  ini  akan menyoroti  kebijakan,  agenda  dan  strategi  Islamdan pemerintahan yang baik dalam menjawab   dua masalah di atas. Temuan studi ini adalah bahwa Islam dan pemerintahan yang baik justru tidak memilikikonsep yang khas, kebijakan, agenda dan  strategi. Sebaliknya, keduanya  jelasmenyepakati bahwa toleransi beragama dan kesetaraan gender penting untukkeberlanjutan  kehidupan manusia. Hasilnya, masyarakat Muslim  harusmenyebarluaskan gagasan kompatibilitas antara Islam dan pemerintahan yangbaik kepada dunia.